2011
DOI: 10.1016/j.amepre.2011.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Exercise After Phase II Cardiac Rehabilitation

Abstract: Background Patients who have completed Phase II cardiac rehabilitation have low rates of maintenance of exercise after program completion, despite the importance of sustaining regular exercise to prevent future cardiac events. Purpose The efficacy of a home-based intervention to support exercise maintenance among patients who had completed Phase II cardiac rehabilitation versus contact control was evaluated. Design An RCT was used to evaluate the intervention. Data were collected in 2005–2010 and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 23 publications
4
87
0
Order By: Relevance
“…6) [20][21][22][23][24][25][26][27] and eight low-quality [7,[28][29][30][31][32][33][34]. Evidence in the 16 studies was conflicting though, as fewer than 75% reported consistent findings.…”
Section: Frequent Telephone Contactmentioning
confidence: 96%
See 1 more Smart Citation
“…6) [20][21][22][23][24][25][26][27] and eight low-quality [7,[28][29][30][31][32][33][34]. Evidence in the 16 studies was conflicting though, as fewer than 75% reported consistent findings.…”
Section: Frequent Telephone Contactmentioning
confidence: 96%
“…Social-cognitive strategies to enhance self-efficacy were used in two studies [29,31,36]. Eleven other studies mentioned using individualized feedback, education or encouragement [10,21,22,24,26,27,29,30,34,37,43]. The studies using a direct remote contact strategy did not report using specific theory-based motivational or coaching strategies [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that interventions which are most effective in promoting PA among cardiac patients include prompt self-monitoring and specific goal setting [4], but reports of pedometer-based interventions have included little methodological detail of how the pedometers were actually used [5][6][7][8]. Other work has reported that patients who engaged in some form of PA at home were more active than those who only engaged in exercise during CR sessions [18] but only 8% of that study's participants reached the recommended minimum level of weekly PA.…”
Section: Intervention (N=19)mentioning
confidence: 99%
“…Recent reviews indicate that interventions which emphasise selfmonitoring, goal setting, identification of barriers to change and consideration of relapse prevention are most likely to yield positive outcomes for patients [3,4]. The use of pedometers in self-monitoring has been reported to be associated with increased levels of PA among cardiac patients [5][6][7][8] but information about how pedometers are actually used in goal setting and self-monitoring is scant. More detail would facilitate the translation of previous findings into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…We almost found no study in contrast with this finding. Although the recommended level of PA for boys is more than girls (28,(30)(31)(32)(33), some social inequalities and social barriers may be the common cause for such differences (34).…”
Section: Discussionmentioning
confidence: 99%